Pre-departure English language preparation of students on joint 2+2 programs. (June 2020) - Bai, Li; Wang, Ying Xian
Abstract: Since 2000, a large number of Sino-foreign joint education programs have been set up. By September 2018, there were 1025 Sino-foreign joint programs at bachelor and above level. Despite the large number of joint programs and their increasing popularity, limited research has examined them. With studies that have looked into joint programs, the focus is mainly on students' after-arrival language challenges, rather than pre-departure language preparation. This study intends to fill the research gap by examining the pre-departure English language preparation of Chinese students on Sino-Australian 2 + 2 joint programs. Twenty-two Chinese students studying at a host Australian university were interviewed to collect qualitative data. Findings show that half of the participants had mixed feelings about their language preparation. Seventeen expressed their appreciation of the effort their Chinese institutions made in improving their English proficiency for overseas study. The greatest areas of improvement according to them were English speaking and writing. However, almost the same number of participants also voiced concerns about the English preparation at their home institutions, including the low level of difficulty of most English courses, limited class hours in oral English, and IELTS-driven nature of some courses. Suggestions for improving the 2 + 2 programs are also discussed.